Establishment of Two Varieties in Tecoma stans of Indian Origin Pharmacognostically and Pharmacologically - Sandhya, K.N.V. Rao*, K. Swarna, David Banji, S. (Journal of Phytology, 2010)
The plant Tecoma stans (L.) Kunth, belongs to family Bignoniaceae and commonly known as â€œPachagotlaâ€ is a dicotyledonous herb popularly grown for its flowers as an ornamental / garden plant in normal gardens and temples. It is also known as Bignonia stans L. Almost all parts of the plant is reported for its medicinal use. This plant is considered to be very effective in the treatment of diabetes. The leaves contain the alkaloids tecomine and tecostamine which is potent hypoglycaemic agent when given intravenously. Anthranilic acid is responsible for the antidiabetic activity, roots are powerful diuretic and vermifuge and tonic. In order to ensure the use of only genuine and uniform material in preparation of herbal formulation, work on standardization was carried out. Morphological and anatomical aspects as well as differential microchemical response have been worked out to identify the diagnostic features of the leaf. Physical constant values involving moisture content, ash and extractives as well as qualitative and quantitative estimation of various phytochemicals have been studied. The presence of alkaloids, carbohydrates, glycosides and proteins were the chemical constituents recorded. Pharmacologically the alpha â€“ glucosidase inhibitory activity of alcoholic and aqueous extracts were carried out by using the goat intestine method. Key words: Tecoma stans, Bignoniaceae, Variant, Diabetes, Alpha â€“ glucosidase <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Rao K N V et al. Establishment of Two Varieties in Tecoma stans of Indian Origin Pharmacognostically and Pharmacologically. J Phytol 2/8 (2010) 92-102.